Male–female separation with a genetic sexing strain of Medfly, Ceratitis capitata, based on the gene sw (slow) - Viscarret, Mariana Mabel; Stolar, Cristian Eric; Cladera, Jorge Luis (lsteg Scientific Publications, 2020)
The rate of development of the Medfly, Ceratitis capitata, slows down in the presence of mutation slow, sw. Separation of fast-developing males from slow-developing females is possible when this locus on chromosome 2 is linked by a translocation to the male determining chromosome Y. We report here the results obtained in an experiment aimed at improving male–female separation by lowering the rearing temperature.Lowtemperature treatmentswere applied to first and second larval stages.This resulted in an increase in the separation in the median time of popping of female and male larvae. The proportion of males accumulated when the females start popping was also affected but to a lesser extent. Experiments on the application of pulses of cold temperature later during larval development are in progress to further improve the separation between sexes using the genetic sexing strain based on the gene sw.